Alimento, afeto e resistência cultural: uma análise dos aspectos fundamentais da identidade de imigrantes sul-coreanos por meio da culinária - Bae, Ester (2024)
This study highlights the importance of Korean cuisine as a cultural expression that maintains the identity of the community in São Paulo. It aims to understand the cultural relationship between food and the construction of collective identity, analyze the extent to which food culture permeates the everyday structural norms of Koreans and their descendants, as well as the social relations within the family and the Korean community. By exploring the complexity of these interrelated factors, it reveals how food acts as an element of preservation of Korean identity in the face of historical and cultural challenges, serving as a link to memory and resistance. The research utilized secondary sources and qualitative and ethnographic work in observing the theme, notably including interviews with Korean women, and, in terms of the theoretical framework, it was based on a phenomenological approach. Among its main findings is the relationship between patriarchal culture and evangelical Protestantism in the Korean commu